Teacher’s Perceptions and Attitudes Toward Bilingualism: Implications For Early Childhood Education - Yilmaz, Hatice Büsra; Karademir, Abdulhamit (Serhat Arslan, 2023)
Bilingual children face various challenges when they start school. They have difficulty communicating with peers and adapting to school and have poor academic performance. This paper investigated teachers’ views of and solutions to problems experienced by bilingual preschoolers. This study adopted a phenomenological research design. The sample consisted of 11 preschool teachers from provinces in Eastern Anatolia and Southeastern Anatolia regions. Data were collected using a semi-structured interview questionnaire developed by the researchers. The data were analyzed using inductive content analysis and presented in Tables with direct quotations from participant opinions. Participants stated that bilingual children had difficulty implementing receptive and expressive language skills, communicating with teachers, and obeying the classroom rules. Participants also noted that they had difficulty with classroom management and educational planning because they could not communicate with bilingual students. However, they reported that their bilingual students developed language skills in the later stages of preschool education. Teachers remarked that parental involvement and collaboration were critical. They advised their colleagues to be mentally and cognitively prepared, perform word-based teaching, collaborate with parents, and make use of books, songs, and rhymes.
Keywords: Studies on Education; Egitim Üzerine Çalismalar